Financial Wind CfDs - Ingmar Schlecht; Lion Hirth; Christoph Maurer (ZBW – Leibniz Information Centre for Economics, 2022)
Contracts for differences are widely discussed as a cornerstone of Europe's future electricity market design. In this paper, we make three contributions to the debate. First, we summarize the dispatch and investment distortions that traditional CfDs cause. Second, we propose an alternative CfD specification that we dub "financial wind CfDs". It is a hybrid between CfDs and forward contracts that aims at being superior to conventional CfDs both in terms of risk mitigation and incentives. Third, we point out that "the other side of the contract", the government's financial position resulting from any long-term contract with generators, must be carefully handled to avoid muting consumers' flexibility incentives or depleting forward markets.
Additional information: *** Final Published Version Available *** : Ingmar Schlecht, Christoph Maurer and Lion Hirth (2024): "Financial contracts for differences: The problems with conventional CfDs in electricity markets and how forward contracts can help solve them", Energy Policy, Volume 186 (March 2024), Article No. 113981, https://doi.org/10.1016/j.enpol.2024.113981; More recent version: doi:10.1016/j.enpol.2024.113981
Keywords: Q4; Q42; 330; electricity market; market design; contracts for differences; energy economics